Emergency responder willingness to respond during disasters: A literature review. (11th June 2021) - Knezek, Erick B.; Vu, Thevu; Lee, Jim
Abstract: Absenteeism of first responders during emergency events is considered a significant issue in disaster response, which is caused by two primary reasons: inability or unwillingness to report to work. This study provides a review of literature related to emergency responders' willingness to respond (WTR) to a disaster. In this review, the history of the genesis, myth and reality periods of WTR research was described. A compilation and analysis of 14 perception studies involving 33, 849 respondents on emergency responder WTR was conducted. Weighted averages method was used to perform descriptive statistical analysis of the compiled surveys. Results showed that, on average, 72.1% of the emergency responders sorted by disaster and 75.1% sorted by role reported they are willing to respond to a disaster. Negative consequences, including concern of home damage, concern for family, and risk to self are the primary barriers to WTR. In contrast, preparedness and a sense of professional duty act as facilitators to WTR.